Elemental: Denise Ferreira da Silva’s Raw Materialist Justice - Joshua Ramey (Religions)
Denise Ferreira da Silva’s recent work, Unpayable Debt, makes a provocative intervention into current debates over and struggles for global justice in the wake of colonialism and in view of contemporary neo-colonial forces of extractive violence. Ferreira da Silva argues that only the return of the total value of the land and labor of the formerly enslaved and colonized would suffice to repay the debt owed to them by the global economy. Yet, such a debt is both unlimited in space and unrestricted in time, since that stolen land and expropriated labor are the very materiality of the global economy, past and present. For Ferreira da Silva, only a truly “raw materialist” apprehension of the scope of this debt, one which appreciates its elemental and cosmic composition, can enable decolonial justice to be conceived or achieved. In this paper, after outlining the arguments of Unpayable Debt, I elaborate Ferreira da Silva’s sense of the elemental stakes of global justice, extending and elaborating her thought through a reading of the recent afro-futurist film Neptune Frost (2021).